Corneal Collagen Cross-Linking (CXL) in Pediatric Keratoconus: Changes in Visual Acuity and Biomechanical Properties: Visual Acuity and Biomechanical Properties - Ganjar Sulaksmono (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Keratoconus is a progressive disease that changes the mechanical shape of the cornea due to thinning of the stromal layer of the cornea. Therefore, early detection and correct management should be able to slow the progression of the disease. This study aimed to compare changes in visual acuity and biomechanic properties of cornea in patients who underwent Corneal Collagen Cross- Linking (CXL) in Dr. Sardjito General Hospital Methods : This is a prospective study that included all pediatric keratoconus patients without any underlying disease that underwent CXL between July 2022 to December 2022. Uncorrected Visual Acuity (UCVA), Best Corrected Visual Acuity (BCVA), Central Corneal Thickness (CCT) and Intraocular Pressure (IOP) were evaluated preoperatively, 2 weeks, and 6 weeks following CXL. Results : Mean age of patients was 11 (range 6-18 y.o). UCVA were 1.00±0.34 logMAR preoperatively, 0.95±0.35 and 0.88±0.37 logMAR at 2 and 6 weeks after CXL (P=0.27 and P=0.02, respectively). BCVA were 0.37±0.28 logMAR preoperatively, 0.46±0.28 and 0.35±0.21 logMAR at 2 and 6 weeks after CXL (P=0.05 and P=0.46, respectively). Mean IOP were 15.21±3.99 preoperatively, 14.45±2.73 and 15.21±3.68 at 2 weeks and 6 weeks after CXL (P=0.33 and P=1.00, respectively). Mean CCT were 503.09±49.43 preoperatively, 508.18±47.68 and 506.82±48.41 at 2 weeks and 6 weeks after CXL (P=0.01 and P=0.11, respectively). No complications occurred during the observation period. Conclusion : UCVA and BCVA were improved after CXL. Analysis showed no significant change for IOP and CCT after CXL procedure. Overall, CXL was safe and significantly improve UCVA and BCVA in pediatric keratoconus.